RELIGIOUS FUNDAMENTALISM AND THE PRESENT CRISIS - V.R. Krishna Iyer, (Journal of Dharma, 1994)
Some friends asked me, "did you sleep well?" "I said, no Indian has the moral right to sleep well." The degradation that is overtaking us so rapidly, alas! in the name of God and religion, deprives us of the relatively little title to live and let other people live. Why does this happen? Recall what Swami Vivekananda had said more than once and with the power of rhetoric which was unique to him? Religions have been responsible for more massacres than any other instrumentality or cause in this world. An yet religion has been so tender as to look after the whole of humanity. We have had the Buddha, who spoke of Karuna, we have had Asoka who spoke of the fellowship of faiths; we have had Jesus whose heart was bleeding for the poor all the time. We have had Mahatma Gandhi who saw divinity in every 'daridra narayana'. And that was why Vivekananda came out with the claim "mathrudevo bhava, pithrudevo bhava." This is what Hindus are used to hearing and uttering. But Vivekananda added to it: "Daridradevo bhava." Blessed are the poor not in heaven, here.